2021
DOI: 10.1016/j.trsl.2020.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to DAMPen COVID-19-mediated lung and systemic inflammation and vascular injury

Abstract: Approximately 15%-20% of patients infected with SARS-CoV-2 coronavirus (COVID-19) progress beyond mild and self-limited disease to require supplemental oxygen for severe pneumonia; 5% of COVID-19-infected patients further develop acute respiratory distress syndrome (ARDS) and multi-organ failure. Despite mortality rates surpassing 40%, key insights into COVID-19-induced ARDS pathology have not been fully elucidated and multiple unmet needs remain. This review focuses on the unmet need for effective therapies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 84 publications
(102 reference statements)
2
37
0
Order By: Relevance
“…But, we did not find any relationship between survival and immunossupresive regimen or CNI's concentration on admission, which is also mentioned by others [11,16] [21]. The phase of hyperinflammation and acute respiratory failure syndrome most frequently precedes multiple organ dysfunction and death [22]. Perhaps effective drugs targeting hyperinflammation could improve COVID-19 outcomes, which remain poor in severe and critical illness.…”
Section: Discussionmentioning
confidence: 43%
“…But, we did not find any relationship between survival and immunossupresive regimen or CNI's concentration on admission, which is also mentioned by others [11,16] [21]. The phase of hyperinflammation and acute respiratory failure syndrome most frequently precedes multiple organ dysfunction and death [22]. Perhaps effective drugs targeting hyperinflammation could improve COVID-19 outcomes, which remain poor in severe and critical illness.…”
Section: Discussionmentioning
confidence: 43%
“…To date, whilst several studies have reported evidence of cellular injury and inflammatory cell death in patients with severe COVID-19 (23,26,222), few have directly screened blood samples for the presence of DAMPs. However, in those that have, significantly elevated levels of the nuclear-derived DAMPs high mobility group box-1 (HMGB-1) and extracellularly-secreted nicotinamide phosphoribosyl-transferase (eNAMPT), as well as mitochondrial-derived DNA (mtDNA) were detected in the plasma of severe COVID-19 patients when compared to HCs and/or mild to moderate COVID-19 cases (205,223,224). Given that N-formylated peptides, which we have shown are responsible for mediating mtDAMP-induced neutrophil tolerance (219), are released alongside mtDNA, then these preliminary data suggest that tolerising mtDAMPs are present in the circulation of patients with severe COVID-19.…”
Section: Neutrophil Tolerance In Severe Covid-19mentioning
confidence: 99%
“…In the setting of non-COVID related ARDS, where elevated BALF concentrations of mtDNA and N-formylated peptides have been implicated in disease pathogenesis ( 225 , 226 ), pharmacological manipulation of mtDAMP signalling has been suggested as a potential treatment for neutrophil-mediated lung injury ( 225 ). Similarly, with the aim of suppressing pulmonary inflammation and preventing the onset of severe disease, blocking DAMP signalling was recently proposed as a treatment for COVID-19 ( 223 , 227 ). We believe that this approach, particularly when focussed upon mtDAMPs, may have the additional benefit of reducing the susceptibility of COVID-19 patients to superinfections by preventing mtDAMP-induced neutrophil tolerance.…”
Section: Neutrophil Tolerance In Severe Covid-19mentioning
confidence: 99%
“…DAMPs probably play a significant role in supporting cytokine storms, but comparatively little research has been expended in studying DAMPs as compared to PAMPs in this context, so the details of what roles DAMPs are playing in maintaining cytokine overproduction syndromes and how to intervene in their effects are vague [ 217 , 218 ]. Critically ill COVID-19 patients, ALI/ARDS patients and sepsis patients all release high levels of extracellular histones (TLR2, TLR4 and NLRP3 activators [ 219 ]); neutrophil elastase (a TLR4 activator [ 220 ]) and cell-free DNA (a TLR9 activator [ 221 ]), each of which correlate with the probability of the patients being admitted to the intensive care unit and of dying [ 222 ].…”
Section: Innate Immune System Receptor Activation In Cytokine Stormentioning
confidence: 99%
“…Other possible DAMPs that may be playing roles in COVID-19 include extracellular RNAs [226] that can activate TLR3 and TLR7, as well as extracellular hemoglobin, which activates NLRP3 and is associated with coagulation dysregulation and microclotting [227,228]. In sum, the activation of TLR2, TLR4, TLR7, TLR9 and NLRP3 are almost certainly maintained by DAMPs in severe COVID-19, ALI/ARDS and sepsis and may need to be therapeutically addressed [217,218,226]. Notably, DAMPs are not known to activate NOD1, NOD2 or RIG1, which might help to explain the absence of their observed activation in established cytokine storm syndromes (Figure 3A-C) as compared with their initial stimulating conditions (Figures 8-10).…”
Section: Role Of Damps In Driving Covid-19 and Other Cytokine Releasementioning
confidence: 99%